Total replacement of solvent in polyurethane synthesis using carbon dioxide soluble 1, 3‐dichlorodistannoxane catalysts. Issue 6 (27th September 2012) - Gartia, Yashraj; Moore, Josh; Felton, Charlette; Pulla, Sharon; Berry, Brian; Munshi, Pradip; Ghosh, Anindya
Abstract This work demonstrates catalytic synthesis of polyurethanes using 1, 3‐dichlorodistannoxane catalysts (1) in carbon dioxide (CO2) and carbon dioxide expanded liquids (CXL). Catalytic polyurethane synthesis was also performed in pure organic solvent (dimethylformamide) for comparison. In this study, mainly, 4, 4′‐methylene‐bis‐(phenyl isocyanate) (MDI) as the diisocyanate precursor and ethylene glycol (EG) as the diol precursor were used for polyurethane synthesis. In addition to MDI, hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), and p‐isocyanatobenzylisocyanate (PIBI) were also used for polyurethane synthesis with different diols or triol in CO2. Polyurethanes with a molecular weight ranging from 3000 to 70, 000 were synthesized depending upon the combination of diisocyanate and diol used. Comparable yields of polyurethanes were obtained using an all butyl group substituted (1a) catalyst in CO2 (55 bars, 50°C) and in DMF (50°C). Additionally, the yield and polydispersity index (PDI) of polymer formed in neat CO2 was comparable with those synthesized in the largely used organic solvent DMF. Interestingly, catalyst 1a in CXL (55 bars, 50°C) gave higher yields, and polymers with lower PDI (1.19). Reactions carried out in scCO2 at 145 bars using PIBI and EG were found to be about three times faster than the reaction carried out in DMF. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013